A cobalt-based complex and a preparation method and application thereof

CN122878359APending Publication Date: 2026-10-09NANYANG INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610949202.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

其中,氢键的作用力弱于配位键,溶剂分子或离子的进出可能会破坏这些氢键,从而影响整个超分子结构的稳定性

Benefits of technology

[0021](1)本发明开拓了钴基配合物材料作为锂离子电池负极材料的应用。通过单晶X-射线衍射仪解析可知述的钴基配合物材料的分子式为Co(tftpa)(im)4(H2O);Co(tftpa)(im)4(H2O)属于单斜晶系,空间群为P21/n,晶胞参数为α=γ=90°,β=90.9340(10)°,V=2392.08(12),Z=4,a=8.6908(3),b=13.5609(4),c=20.2995(5)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878359A_ABST
    Figure CN122878359A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of complex materials, and discloses a cobalt-based complex and a preparation method and application thereof.A cobalt-based complex has a molecular formula of Co(tftpa)(im)4(H2O), metal cobalt is a six-coordinated structure, is respectively coordinated with one oxygen atom from tftpa, four nitrogen atoms from four imidazole ligands im and one oxygen atom from a water molecule, and forms a mononuclear structure; the Co(tftpa)(im)4(H2O) belongs to a monoclinic system, a space group is P21 / n, cell parameters are alpha = gamma = 90 DEG, beta = 90.9340(10) DEG, V = 2392.08(12), Z = 4, a = 8.6908(3), b = 13.5609(4), c = 20.2995(5). The method is simple, and when the Co(tftpa)(im)4(H2O) is applied to a lithium ion battery as a negative electrode material, high specific capacity and good cycle stability are exhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coordination materials, and particularly relates to a cobalt-based coordination compound. Background Technology

[0002] With the continued depletion of traditional fossil fuels and the increasingly severe ecological and environmental problems, the global energy structure is facing a major transformation. Against this backdrop, clean and renewable energy sources such as wind, solar, hydropower, and tidal power, which possess advantages such as sustainability, safety, environmental friendliness, and wide distribution, have experienced rapid development. However, these new energy sources are limited by natural conditions, exhibiting instability and intermittency. Therefore, developing and utilizing these new energy sources requires vigorous development of energy storage technologies to achieve peak shaving and valley filling, thereby improving their energy quality.

[0003] Currently, energy storage technologies applied to new energy sources can be mainly divided into physical energy storage and chemical energy storage. Physical energy storage includes pumped hydro storage, compressed air storage, flywheel energy storage, and molten salt energy storage. Chemical energy storage involves converting electrical energy into chemical energy for storage, primarily through methods such as hydrogen production via water electrolysis, converting electrical energy into stable chemical energy; and electrochemical energy storage using secondary batteries or supercapacitors. Secondary batteries, including lead-acid batteries, flow batteries, and lithium-ion batteries, hold a significant market share in the energy storage field due to their high energy density, energy conversion efficiency, and responsiveness. Lithium-ion batteries (LIBs), in particular, have been widely used in the 3C market and power batteries due to their high energy density and portability, but currently commercially available LIBs are insufficient to meet consumers' daily needs. Electrode materials are a crucial component of LIBs, playing a vital role in binding lithium during the "rocking chair cycle." Therefore, designing novel electrode materials has become the optimal choice for improving the energy storage performance of LIBs.

[0004] Studies have shown that inorganic electrode materials, represented by transition metal oxides and graphite, and traditional commercial lithium-ion batteries based on them, have solved the safety issues associated with lithium metal batteries to a certain extent. However, the theoretical capacity of these materials is difficult to increase further; at the same time, the mineral resources required for material preparation are unevenly distributed on Earth and are expensive. Furthermore, the mining and preparation processes require energy-intensive processes such as high-temperature sintering and generate environmental pollution. Organic electrode materials possess advantages such as high theoretical specific capacity, abundant and readily available resources, low energy consumption in synthesis, and green recyclability. However, due to the "like dissolves like" mechanism, organic electrode materials are easily soluble in organic electrolytes such as carbonates, causing a sharp decrease in their cycle capacity and even direct battery failure. In addition, most organic electrode materials have low inherent conductivity, resulting in low material utilization and poor rate performance; furthermore, the electrode potential of organic electrode materials is difficult to meet the actual usage requirements of the positive and negative electrodes, requiring optimization. Therefore, the research and optimization of electrode materials still need continuous development. Developing high-performance lithium-ion battery electrode materials is of significant research importance.

[0005] Coordination polymers (CPPs) are mainly composed of metal nodes / clusters and organic linkers, exhibiting flexible designability, ordered spatial structures, and high specific surface areas. This structural approach and spatial composition facilitate electrolyte wetting and lithium-ion transport. The capacity of CPPs primarily derives from organic ligands and metal sites; therefore, the flexible designability of CPP molecules allows for optimization of molecular structures to meet desired capacities. Several years after the concept of coordination polymers was proposed, reports emerged of their direct application in electrode materials. For example, Chen's team first reported on MOF-177 as a lithium storage anode in 2006, achieving an initial discharge specific capacity of approximately 425 mAh g⁻¹ and an initial charge specific capacity of approximately 110 mAh g⁻¹ at a current density of 50 mA g⁻¹, with high irreversible capacity. In 2007, Tarascon et al. first investigated the performance of MIL-53(Fe) as a lithium storage cathode material. During charge and discharge processes, Fe… 3+ Partially reduced to Fe 2+ At a current density of 1 / 40 C, the specific capacity is 75 mAh g⁻¹, which is relatively low. Wang Qinghua et al. disclosed a complex in which cobalt directly coordinates with the six nitrogen atoms of six imidazole molecules to form an octahedral ligand structure [M(ImH)₆](tfbdc) (M = Co, Ni). 2+ Cations and TFBDC 2- Three-dimensional supramolecular structures are formed by interconnected molecules through hydrogen bonding. However, hydrogen bonds are weaker than coordination bonds, and the entry or exit of solvent molecules or ions can disrupt these hydrogen bonds, thus affecting the stability of the entire supramolecular structure. Furthermore, tfbdc 2-The anion does not directly participate in cobalt coordination; during electrochemical performance testing, electrons are required in [Co(ImH)6]. 2+ The "jumping" transmission between units undoubtedly increases resistance, reduces the overall conductivity of the material, and thus affects its electrochemical performance when in use.

[0006] In summary, existing technologies suffer from two main problems: First, due to the instability of active sites and crystal structure, coordination polymers become amorphous during charge-discharge cycles, leading to rapid capacity decay. Second, due to the inherent electronic insulation properties of most coordination polymers, their cycle performance and rate performance are difficult to meet requirements.

[0007] Therefore, in order to further improve battery capacity, cycle stability and rate performance, it is crucial to develop a novel coordination polymer with good intrinsic reversibility and a relatively stable structure. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention proposes a cobalt-based complex, its preparation method, and its application.

[0009] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0010] A cobalt-based complex with the molecular formula Co(tftpa)(im)4(H2O) has a six-coordinate structure, which coordinates with an oxygen atom from tetrafluoroterephthalic acid tftpa, four nitrogen atoms from four imidazole ligands im, and an oxygen atom from a water molecule to form a mononuclear structure. Co(tftpa)(im)4(H2O) belongs to the monoclinic crystal system with space group P21 / n and cell parameters α=γ=90°, β=90.9340(10)°, V=2392.08(12), Z=4, a=8.6908(3), b=13.5609(4), c=20.2995(5).

[0011] The preparation method of the above cobalt-based complex is as follows: cobalt salt and tetrafluoroterephthalic acid are dissolved in solvent A, and imidazole solution is added and mixed to obtain a mixed solution; the mixed solution is reacted to obtain the cobalt-based complex.

[0012] Furthermore, the molar ratio of cobalt salt, tetrafluoroterephthalic acid, and imidazole in the above mixed solution is (0.4-1.5):(1-3):(0.4-1.5). The concentration of tetrafluoroterephthalic acid in the mixed solution is 0.02-0.06 mol / L.

[0013] Solvent A is anhydrous ethanol, methanol, or a mixture of methanol and ethanol, and the solvent for the imidazole solution is deionized water. The volume ratio of solvent A to deionized water is (2-3):1.

[0014] The cobalt salts mentioned above are cobalt nitrate hexahydrate (Co(NO3)2‧6H2O), cobalt chloride hexahydrate (CoCl2‧6H2O), or cobalt acetate hexahydrate.

[0015] The above-mentioned reactions refer to reactions that can be achieved by either standing at room temperature or by heating. Standing at room temperature involves a temperature of 15-30℃ for 4-20 days. Heating involves a temperature of 60-90℃ for 6-14 hours.

[0016] The above-mentioned cobalt-based complexes are used in lithium-ion battery anode materials.

[0017] Specifically, in the above applications, the preparation steps of lithium-ion batteries are as follows:

[0018] (1) Preparation of working electrode (negative electrode): The cobalt-based complex material Co(tftpa)(im)4(H2O) crystal prepared in this invention is dried in a vacuum oven at 60-90 ℃ for 8-12 h. Then, the dried cobalt-based complex material is weighed at a mass ratio of 6:3:1, and the conductive agent (ketjen black) and binder (polyvinylidene fluoride) are ground and mixed evenly. The mixture is then prepared into a slurry with a solvent (N-methylpyrrolidone), coated onto copper foil, and dried under vacuum at 60-80 ℃ for 10-12 h. The resulting electrode is sliced ​​to obtain a circular electrode sheet. The obtained electrode sheet is sliced ​​into a circular electrode sheet using an MSK-T10 manual slicer with a mold diameter of 12 mm, and weighed for later use.

[0019] (2) Battery assembly: In a glove box filled with argon gas, the negative electrode sheet obtained in step (1) is used as the negative electrode of the battery, the lithium sheet is used as the positive electrode, the separator is Celgard 2400, and the electrolyte is a mixed solution of LiPF6 (EC+DEC) with a concentration of 1 mol / L, wherein EC is ethylene carbonate, DEC is diethyl carbonate, and the volume ratio of EC to DEC is 1:1. The battery is assembled into a CR2032 button cell.

[0020] The beneficial effects of this invention are:

[0021] (1) This invention has pioneered the application of cobalt-based complex materials as negative electrode materials for lithium-ion batteries. The molecular formula of the cobalt-based complex material described is Co(tftpa)(im)4(H2O) as determined by single-crystal X-ray diffraction. Co(tftpa)(im)4(H2O) belongs to the monoclinic crystal system, space group P21 / n, and cell parameters are α=γ=90°, β=90.9340(10)°, V=2392.08(12), Z=4, a=8.6908(3), b=13.5609(4), c=20.2995(5).

[0022] (2) When the cobalt-based complex material Co(tftpa)(im)4(H2O) is used as the negative electrode material in the field of lithium-ion batteries, it exhibits high specific capacity and good cycle stability. At a current density of 100 mA / g, the initial charge and discharge capacities are 1132 and 1765 mAh / g, respectively. After 100 charge-discharge cycles, its specific capacity stabilizes at around 1056 mAh / g, with a coulombic efficiency of 99.3%. After 500 cycles at 500 mA / g, the capacity remains at around 752 mAh / g. Furthermore, it also exhibits good rate performance at different rates. Constant current charge-discharge was performed at current densities of 100 mA / g, 200 mA / g, 500 mA / g, 1000 mA / g, and 2000 mA / g, and 10 cycles were performed at each rate. The average capacity values ​​were 1078 mAh / g, 988 mAh / g, 877 mAh / g, 811 mAh / g, and 750 mAh / g, respectively. When the current density returned to 100 mA / g, the capacity was still as high as 1020 mAh / g, demonstrating the material's excellent rate performance. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a coordination environment diagram of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of the present invention.

[0025] Figure 2 The X-ray powder diffraction pattern of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention.

[0026] Figure 3 The image shows a scanning electron microscope (SEM) image of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention.

[0027] Figure 4 The image shows the appearance of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention.

[0028] Figure 5 The constant current charge-discharge diagram shows the cobalt-based complex Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention as a negative electrode material for lithium-ion batteries.

[0029] Figure 6 The charge-discharge cycle diagram of the cobalt-based complex Co(tftpa)(im)4(H2O) lithium-ion battery anode material prepared in Example 1 of the present invention at a current density of 100 mA / g.

[0030] Figure 7 The charge-discharge cycle diagram of the cobalt-based complex Co(tftpa)(im)4(H2O) lithium-ion battery anode material prepared in Example 1 of this invention is shown at a current density of 500 mA / g.

[0031] Figure 8 The graph shows the rate performance of the cobalt-based complex Co(tftpa)(im)4(H2O) lithium-ion battery anode material prepared in Example 1 of this invention. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Example 1

[0034] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0035] Cobalt acetate hexahydrate (0.1 mmol) and tetrafluoroterephthalic acid (0.2 mmol) were dissolved in 4 mL of anhydrous ethanol. Imidazole (0.0681 g, 0.1 mmol) was dissolved in 2 mL of deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous, clear solution, which was then allowed to stand at room temperature for 7 days to evaporate. After the reaction was complete, the solution was washed three times with 20 mL of distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O). The coordination environment diagram of the cobalt-based complex Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention is shown below. Figure 1 .

[0036] Transparent, crack-free crystals were selected under a microscope, and their crystal structures were determined using a Supernova X-ray single-crystal diffractometer. Mo-Kα rays monochromated by a graphite monochromator were used as the incident radiation source, and diffraction points were collected in a scanning manner. The coordinates and anisotropy parameters were corrected by the least squares method. The positions of hydrogen atoms were obtained by theoretical hydrogen addition. All calculations were performed using SHELXL-97 and the SHELXL-97 software package. The results showed that the molecular formula of the metal-organic framework was a cobalt-based complex Co(tftpa)(im)4(H2O), belonging to the monoclinic crystal system, space group P21 / n, and cell parameters α=γ=90°, β=90.9340(10)°, V=2392.08(12), Z=4, a=8.6908(3), b=13.5609(4), c=20.2995(5). In the cobalt-based complex Co(tftpa)(im)4(H2O), each metallic Co is a six-coordinate structure, which coordinates with four nitrogen atoms from four imidazole ligands, one oxygen atom from tetrafluoroterephthalic acid, and one oxygen atom from a water molecule, forming a mononuclear structure.

[0037] Figure 2 The image shows the X-ray powder diffraction pattern of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention. As can be seen from the image, the diffraction patterns of the synthesized samples are consistent with the X-ray diffraction patterns of the simulated samples, indicating high purity of the compound.

[0038] Figure 3 This is a scanning electron microscope image of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention. The study revealed that the cobalt-based complex exhibits a regular blocky structure.

[0039] Figure 4 This image shows the crystal appearance of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention. The study revealed that the cobalt-based complex exhibits a regular blocky structure.

[0040] Example 2

[0041] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0042] Cobalt acetate hexahydrate (0.15 mmol) and tetrafluoroterephthalic acid (0.3 mmol) were dissolved in 5 mL of anhydrous ethanol. Imidazole (0.15 mmol) was dissolved in 2 mL of deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous and clear solution, which was then allowed to stand at room temperature for 10 days to evaporate. After the reaction was complete, the solution was washed three times with 20 mL of distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O).

[0043] Example 3

[0044] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0045] Cobalt acetate hexahydrate (0.1 mmol) and tetrafluoroterephthalic acid (0.3 mmol) were dissolved in a mixed solvent of 3 mL anhydrous ethanol and 2 mL methanol. Imidazole (0.15 mmol) was dissolved in 3 mL deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous and clear solution, which was then allowed to stand at room temperature for 10 days to evaporate. After the reaction was complete, the solution was washed three times with 20 mL distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O).

[0046] Example 4

[0047] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0048] Cobalt acetate hexahydrate (0.15 mmol) and tetrafluoroterephthalic acid (0.3 mmol) were dissolved in a mixed solvent of 3 mL anhydrous ethanol and 2 mL methanol. Imidazole (0.15 mmol) was dissolved in 2 mL deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous and clear solution, and the reaction was carried out at 80 °C for 12 h. After the reaction was completed, the solution was washed three times with 20 mL distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O).

[0049] Example 5

[0050] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0051] Cobalt chloride hexahydrate (0.4 mmol) and tetrafluoroterephthalic acid (1 mmol) were dissolved in a mixed solvent of 9 mL anhydrous ethanol and 3 mL methanol. Imidazole (0.4 mmol) was dissolved in 4 mL deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous and clear solution, and the reaction was carried out at 90 °C for 6 h. After the reaction was completed, the solution was washed three times with 20 mL distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O).

[0052] Example 6

[0053] The preparation method of the cobalt-based complex (Co(tftpa)(im)4(H2O)) in this embodiment is as follows:

[0054] Cobalt acetate hexahydrate (0.15 mmol) and tetrafluoroterephthalic acid (0.3 mmol) were dissolved in a mixed solvent of 6 mL anhydrous ethanol and 4 mL methanol. Imidazole (0.15 mmol) was dissolved in 5 mL deionized water. The two solutions were mixed under magnetic stirring to obtain a homogeneous and clear solution, and the reaction was carried out at 60 °C for 14 h. After the reaction was completed, the solution was washed three times with 20 mL distilled water to obtain brick-red blocky crystals of Co(tftpa)(im)4(H2O).

[0055] Application examples

[0056] The cobalt-based complex (Co(tftpa)(im)4(H2O)) prepared in this invention is used in lithium-ion battery anode materials. The specific preparation method of the material is as follows:

[0057] (1) Preparation of lithium battery anode material: The cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in this invention is heated at 70°C for 12 h in a vacuum drying oven to obtain the active material of lithium battery anode.

[0058] (2) Preparation of lithium battery negative electrode sheet: Cobalt-based complex material Co(tftpa)(im)4(H2O) crystal, conductive agent (ketjen black) and binder (PVDF) were weighed in a mass ratio of 6:3:1, ground and mixed evenly, and slurry was prepared with solvent (NMP). The slurry was coated on copper foil and dried under vacuum at 80℃ for 12 h. The resulting electrode sheet was sliced ​​to obtain a circular electrode sheet. The obtained electrode sheet was sliced ​​into a circular electrode sheet using an MSK-T10 manual slicer with a mold diameter of 12 mm, and weighed for later use.

[0059] (3) Assemble lithium-ion batteries: Lithium sheets are used as counter electrodes, Celgard 2400 membranes are used as separators, 1 mol / L lithium hexafluorophosphate (LiPF6) is used as electrolyte, and the electrolyte is a mixture of ethylene carbonate (EC): diethyl carbonate (DEC) in volume ratio of 1:1. The circular electrode sheet obtained in step (2) is used as the negative electrode to assemble lithium-ion button batteries. The battery model is CR2032.

[0060] The assembled lithium-ion button batteries were subjected to constant current charge-discharge tests, cycle stability tests, and rate performance tests.

[0061] Electrochemical performance tests were conducted using the Xinwei Battery Testing System, model CT-4008Th-5V10mA-164. The testing temperature was kept constant at 25℃, and the charge / discharge cutoff voltage ranged from 0.01 to 3.0 V. Cycling performance tests were performed with 150 charge / discharge cycles at a current density of 100 mA / g and 500 charge / discharge cycles at a current density of 500 mA / g. Rate performance tests were conducted at constant current charge / discharge densities of 100 mA / g, 200 mA / g, 500 mA / g, 1000 mA / g, 2000 mA / g, and 100 mA / g, with 10 cycles at each rate.

[0062] Figure 5 The figure shows the galvanostatic charge-discharge curve of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention as a lithium-ion battery anode material. As can be seen from the figure, the lithium-ion battery prepared using this anode material has a charge-discharge plateau below 1 V, indicating a relatively low plateau and demonstrating that the lithium-ion battery anode material prepared by the method described in this invention has excellent electrochemical performance. At a current density of 100 mA / g, the initial charge and discharge capacities are 1132 mAh / g and 1765 mAh / g, respectively.

[0063] Figure 6 The charge-discharge cycle diagram of the cobalt-based complex material Co(tftpa)(im)4(H2O) lithium-ion battery anode material prepared in Example 1 of the present invention at a current density of 100 mAh / g. Figure 7 The image shows the charge-discharge cycle diagram of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention as a lithium-ion battery anode material at a current density of 500 mA / g. Figure 6 and Figure 7It can be seen that at a current density of 100 mA / g, after 100 charge-discharge cycles, its specific capacity stabilizes at around 1056 mAh / g, and its coulombic efficiency is 99.3%; after 500 cycles at 500 mA / g, the capacity remains at 752 mAh / g.

[0064] Figure 8 The graph shows the rate performance of the cobalt-based complex material Co(tftpa)(im)4(H2O) prepared in Example 1 of this invention as a negative electrode material for lithium-ion batteries. It exhibits good rate performance at different rates. Constant current charge-discharge was performed at current densities of 100 mA / g, 200 mA / g, 500 mA / g, 1000 mA / g, and 2000 mA / g, and cyclically for 10 cycles at each rate. The average capacity values ​​were 1078 mAh / g, 988 mAh / g, 877 mAh / g, 811 mAh / g, and 750 mAh / g, respectively. When the current density returned to 100 mA / g, the capacity was still as high as 1020 mAh / g, demonstrating excellent rate performance.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A cobalt-based complex, characterized in that, The molecular formula of the cobalt-based complex is Co(tftpa)(im)4(H2O). The metallic cobalt has a six-coordinate structure, which coordinates with one oxygen atom from tetrafluoroterephthalic acid tftpa, four nitrogen atoms from four imidazole ligands im, and one oxygen atom from a water molecule to form a mononuclear structure. Co(tftpa)(im)4(H2O) belongs to the monoclinic crystal system, with space group P21 / n and cell parameters α=γ=90°, β=90.9340(10)°, V=2392.08(12), Z=4, a=8.6908(3), b=13.5609(4), c=20.2995(5).

2. The method for preparing the cobalt-based complex according to claim 1, characterized in that, The steps are as follows: Dissolve cobalt salt and tetrafluoroterephthalic acid in solvent A, add imidazole solution and mix to obtain a mixed solution; react the mixed solution to obtain a cobalt-based complex.

3. The method for preparing the cobalt-based complex according to claim 2, characterized in that, The molar ratio of cobalt salt, tetrafluoroterephthalic acid and imidazole in the mixed solution is (0.4-1.5):(1-3):(0.4-1.5).

4. The method for preparing the cobalt-based complex according to claim 3, characterized in that, The concentration of tetrafluoroterephthalic acid in the mixed solution is 0.02-0.06 mol / L.

5. The method for preparing the cobalt-based complex according to claim 4, characterized in that, The cobalt salt is any one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, and cobalt acetate hexahydrate.

6. The method for preparing the cobalt-based complex according to claim 4, characterized in that, Solvent A is anhydrous ethanol, methanol, or a mixture of methanol and ethanol, and the solvent for the imidazole solution is deionized water.

7. The method for preparing the cobalt-based complex according to claim 6, characterized in that, The volume ratio of solvent A to deionized water is (2-3):

1.

8. The method for preparing the cobalt-based complex according to claim 6, characterized in that, The reaction refers to a process that can be carried out by standing at room temperature or by heating.

9. The method for preparing the cobalt-based complex according to claim 8, characterized in that, The time for standing at room temperature is 4-20 days; the temperature for heat treatment is 60-90℃ and the time is 6-14 hours.

10. The application of the cobalt-based complex according to claim 1 in lithium-ion battery anode materials.